ANALISIS KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA SMP PADA MATERI BANGUN DATAR - Nur Azizah Kamalia; Redo Martila Ruli (Department of Mathematics Education, Universitas Kuningan, 2022)
This study aims to describe the mathematical creative thinking ability of class VIII junior high school students in one of the schools in Karawang district in solving problems related to the material of flat shapes. This study uses a qualitative approach with a descriptive method. The subjects in this study were 16 students of class VIII in one of the junior high schools in Karawang Regency. The instrument used was in the form of a mathematical creative thinking ability test consisting of four essay questions and interview guidelines. The data collection techniques used in this research were tests and interviews. The data analysis technique used in this study consisted of data reduction, data presentation, and conclusion drawing. Based on the results and discussion of this study, it shows that the test results of students creative thinking skills are 25% in the high category with 4 students, 31.25% in the medium category with 5 students, and 43.75% in the low category. with a total of 7 students. So it can be concluded that the mathematical creative thinking ability of SMP class VIII students at one of the schools in Karawang district is still relatively low, and students also have not met the indicators of creative thinking skills, namely fluency, flexibility, originality, and elaboration